BCRNet-SNN: Body Channel Response-Aware Spiking Neural Network for User Recognition - Kang, Taewook; Shin, Chanwoo; Lee, Jongseok; Lee, Jae-Jin; Sim, Donggyu; Kim, Seong-Eun (IEEE transactions on industrial informatics, 2025)
Spiking neural networks (SNNs) have been recently highlighted as an attractive approach for implementing artificial intelligence models in resource-constrained edge devices for various industrial applications. These SNNs leverage low-power and wide dynamic range processing through biologically inspired event-driven operations in a massively parallel manner. In this respect, we propose BCRNet-SNN, an SNN model designed to utilize an electric body channel response (BCR) as a biometric feature for user recognition, where each element in the BCR dataset for 15 subjects is a 1-D vector comprising 380 feature points from the measured envelope by applying chirp signals to the body. The network parameters for implementing the posttrained BCRNet-SNN are inherited from the proposed convolutional neural network (CNN) that extensively extracts BCR-based biometric features (BCRNet), followed by applying knowledge distillation-based network lightening process on BCRNet. The performance evaluation results compared to ResNet18 and ResNet6 for the BCR dataset show that BCRNet achieves a greater than 2 % and 1.4 % improvement, respectively, in the average classification accuracy, while significantly reducing the number of network parameters to less than 1 % . The student network distilled from the teacher BCRNet (BCRNet-S) requires only 5.1 % network parameters than BCRNet, which can be eligible for implementation in BCRNet-SNN. The proposed structure of BCRNet-SNN to effectively accommodate the CNN-to-SNN-converted parameters from BCRNet-S can achieve up to a maximum accuracy of 98.11 % , without observable performance degradation compared to BCRNet.